2020
DOI: 10.1177/1535370219896545
|View full text |Cite
|
Sign up to set email alerts
|

Nonlabeling and quantitative assessment of chondrocyte viability in articular cartilage with intrinsic nonlinear optical signatures

Abstract: Chondrocyte viability is a crucial factor for evaluating cartilage health. Most prevalent cell viability assays rely on dyes and are not applicable for in vivo or longitudinal studies. Here we demonstrated that the two-photon excited autofluorescence and second harmonic generation microscopy provided high-resolution imaging of cartilage tissue and distinguished live/dead chondrocytes by visual assessment. Furthermore, the normalized autofluorescence ratio was proposed as a quantitative indicator to determine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…The improvement is more prominent when using wMCV-Net. The contribution from the SHG channel was also found in our previous study, where populations of live and dead cells could be better separated according to the NAD(P)H and FPs ratios if the SHG channel was used to reduce the autofluorescence contribution from collagen in the ECM region 16 . The usefulness of the SHG channel in CV analysis is perhaps due to the overall improvement of the contrast between cells and the ECM area.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The improvement is more prominent when using wMCV-Net. The contribution from the SHG channel was also found in our previous study, where populations of live and dead cells could be better separated according to the NAD(P)H and FPs ratios if the SHG channel was used to reduce the autofluorescence contribution from collagen in the ECM region 16 . The usefulness of the SHG channel in CV analysis is perhaps due to the overall improvement of the contrast between cells and the ECM area.…”
Section: Discussionsupporting
confidence: 67%
“…Our studies with freshly excised cartilage tissue from rat tibias 16 showed that live chondrocytes exhibited higher intensity of autofluorescence from NAD(P)H than dead chondrocytes did. We found that the ratio between NAD(P)H and NAD(P)H+FPs emission was a robust measure to differentiate live and dead chondrocytes.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…An inverted Olympus FV1200MPE multiphoton laser scanning microscope (Olympus, Center Valley, PA) with a ×10 lens was used for imaging. The excitation wavelength was 800 nm 56 . The green fluorescence signal was collected within the 495–540 nm range while red fluorescence signal was collected in the 575–630 nm range.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al. 76 investigated application of intrinsic nonlinear optical imaging such as two-photon excited autofluorescence and second harmonic generation (SHG) microscopy to quantitatively assess chondrocyte viability in articular cartilage. Lu et al.…”
mentioning
confidence: 99%